Developing Systems Thinking Skills with a Global Climate Change Module: A Mixed Methods Design - Sevgi Aslıhan Karayol; Ünsal Umdu Topsakal (Education Sciences)
Global climate change is an important, complex problem worldwide. Systems thinking skills enable us to solve complex problems from a holistic perspective. Based on this relationship, in this study, we aimed to investigate the effect of a systems thinking based global climate change module on students’ systems thinking skills. A mixed method explanatory design was used with 104 eighth grade students in Turkey. The systems thinking based global climate change module was implemented face to face with first group and with a blended learning method with second group. Activities for a control group were designed according to the curriculum objectives. Students’ systems thinking skills were analyzed quantitatively with the Systems Thinking Skills Test and qualitatively with document analysis. The results showed that the students who used the module, regardless of the implementation method, increased their systems thinking skills significantly, providing more complex answers, ideas, and solutions regarding issues associated with global climate change. The new generation will have to cope with the complex problems of today’s world and produce solutions to them. Therefore, it is recommended that their systems thinking skills be supported by different disciplines, thus developing a holistic approach.